Novel insights into laser glass processing: Exploring base material influence for surface modification - Rai, Rahool; M., Ishak; Quazi, M. M. (Elsevier, 2026)
Dealing with glass at a 1064 nm wavelength can be tricky because glass does not absorb much energy at this wavelength, making direct laser patterning a bit of a challenge. In this study, a new chemical-free way to mark 1 mm soda-lime glass using pulsed fiber lasers was explored. A metallic substrate underneath the glass is used while adjusting the laser frequencies to achieve unique surface changes specifically wettability. Overlapping tracks, grooves, and recast layers were observed, which suggest localized melting and re-solidification due to interactions between the plume and materials, as well as varying energy absorption. SEM and EDS analyses showed that Zn and Fe vapours from the base materials were redeposited, indicating strong thermal interactions. The process induces surface structuring and carbon enrichment, suggesting plume shielding effects and atmospheric incorporation. However, the glass nearly achieved hydrophobic state, with water contact angles increasing from 42° to 80°, likely due to carbon buildup. Despite these variations, the glass retained its optical transparency, with only a slight darken at higher frequencies. These results signify the influence of base material for laser-glass passive interactions and offer a scalable way to functionalize transparent materials without requiring coatings or hazardous chemical pretreatments.